2019
DOI: 10.1111/jspn.12234
|View full text |Cite
|
Sign up to set email alerts
|

Opportunities for nurses to support recovery after pediatric injury: Relationships among posttraumatic stress, hope, and quality of life

Abstract: Purpose Nurses are at the forefront of children's postinjury recovery; this unique role provides an opportunity for nurses to recognize and screen for symptoms that may interfere with children's quality of life (QOL). As such, aims of the present investigation were to explore selected variables (e.g., posttraumatic stress symptoms [PTSS], hope) that have the potential to impact QOL after pediatric injury, with a larger goal of contributing to recommendations for nursing practice to support children's full (phy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“… 7 , 11 Previous study also demonstrated that nurses in clinical settings were uniquely positioned to integrate aspects of TIC principles into their daily practice so as to minimize patients’ traumatic symptom and promote recovery. 36 It reinforces the need to increase nurses’ competence in responding to the trauma-exposed patients in a trauma-informed manner. The knowledge, attitude and practice were the important parts of individual competency in the delivery of TIC.…”
Section: Discussionmentioning
confidence: 82%
“… 7 , 11 Previous study also demonstrated that nurses in clinical settings were uniquely positioned to integrate aspects of TIC principles into their daily practice so as to minimize patients’ traumatic symptom and promote recovery. 36 It reinforces the need to increase nurses’ competence in responding to the trauma-exposed patients in a trauma-informed manner. The knowledge, attitude and practice were the important parts of individual competency in the delivery of TIC.…”
Section: Discussionmentioning
confidence: 82%